A mulher e a agricultura quilombola no Vale do Ribeira (SP): narrativas sobre conhecimento, memória e cotidiano - Haiala, Leticia de Assis (Universidade Federal de São Carlos, 2021)
This study discusses aspects of the quilombola cultivation in the Ribeira Valley from the women’s perspective, their praxis, knowledge, and memory. The research was based on an anthropological-oriented ethnoecological approach. The fieldwork was carried out between July 2019 and January 2020, totalizing 21 days in the Pedro Cubas and Pedro Cubas de Cima communities. The routine of ten women aged between 28 and 76 years old was registered, in addition to the application of semi-structured interviews and questionaries. The results show that the cultivation among the interviewees is practiced near the house, in the ‘terreiro’, as well as far away from it, in the ‘capuovas’. Fifty-seven kinds of cultivated foods were reported, among which the most common were beans, cassava, maize, chicory, lettuce, banana, and peach palm. The use of synthetic and organic agricultural inputs is present. Traditional knowledge and cultivation techniques, such as consortium planting, respect for the lunar calendar, and the fallow system, are still present among the women. At the magic-religious dimension, ‘simpatias’ for pest control in the field were reported, in addition to the interdictions to the women in the field due to their physiological cycles. Beyond the ethnographic features herein presented, the set of perceptions, narratives, knowledge, and ontological references discussed may also subsiding governmental policies for quilombolas’ women in the region.
Women and quilombola agriculture in Vale do Ribeira (SP): narratives about knowledge, memory and daily life.
Keywords: Agricultura quilombola; Mulheres quilombolas; Mata atlântica; Quilombola agriculture; Quilombola women; Atlantic forest; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA